2015
DOI: 10.1039/c4cc08749f
|View full text |Cite
|
Sign up to set email alerts
|

Self-reduction of a copper complex MOD ink for inkjet printing conductive patterns on plastics

Abstract: Highly conductive copper patterns on low-cost flexible substrates are obtained by inkjet printing a metal complex based ink. Upon heating the ink, the soluble complex, which is composed of copper formate and 2-amino-2-methyl-1-propanol, decomposes under nitrogen at 140 °C and is converted to pure metallic copper. The decomposition process of the complex is investigated and a suggested mechanism is presented. The ink is stable in air for prolonged periods, with no sedimentation or oxidation problems, which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
139
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(143 citation statements)
references
References 31 publications
(4 reference statements)
4
139
0
Order By: Relevance
“…16−18 However, the band was believed to be due to adsorbed or atmospheric CO 2 traces because it was observed from the start (100°C) with no decomposition of the carboxyl group and it disappeared gradually at an elevated temperature with the decomposition and volatilization of the carboxyl group. Furthermore, the intensity of the bands at 1590 cm 18 The growth of Cu in 1:1 and 1:3 inks can be speculated from the decrease in a whole range of transmittance intensities in the time-resolved in situ FTIR spectra during the thermal heating, because a metallic Cu reflects the IR light. As shown in Figure 4, the IR transmittance of 1:1 ink started to decrease dramatically after ∼4 min of heating and stopped after ∼5.7 min of heating, while that of 1:3 ink dropped mainly from ∼5 to ∼6.7 min of heating, indicating the significant growth of Cu nuclei in both inks.…”
Section: Resultsmentioning
confidence: 98%
“…16−18 However, the band was believed to be due to adsorbed or atmospheric CO 2 traces because it was observed from the start (100°C) with no decomposition of the carboxyl group and it disappeared gradually at an elevated temperature with the decomposition and volatilization of the carboxyl group. Furthermore, the intensity of the bands at 1590 cm 18 The growth of Cu in 1:1 and 1:3 inks can be speculated from the decrease in a whole range of transmittance intensities in the time-resolved in situ FTIR spectra during the thermal heating, because a metallic Cu reflects the IR light. As shown in Figure 4, the IR transmittance of 1:1 ink started to decrease dramatically after ∼4 min of heating and stopped after ∼5.7 min of heating, while that of 1:3 ink dropped mainly from ∼5 to ∼6.7 min of heating, indicating the significant growth of Cu nuclei in both inks.…”
Section: Resultsmentioning
confidence: 98%
“…32 These organic copper complexes can decompose at temperatures as low as 100 C. 32,33 Moreover, with a low sintering temperature, one can also print the copper MOD ink on plastic sheets to make exible conductive patterns. 28 These frontier studies have shown great feasibility of copper MOD ink formulation for conductive copper thin lms. However, although those copper complexes can decompose into metals at low temperatures, the copper MOD inks are regularly found to have strong dewetting 29 or surface morphological problems 32 during the thermal calcination process.…”
Section: -29mentioning
confidence: 99%
“…In the printing technique, an ink or paste containing active materials is printed and then sintered to form conductive patterns or films. This makes the method cost-effective, highly efficient in terms of material usage, scalable and simple in terms of processing, and flexible for use on various types of substrates123. Many examples have been reported for using metallic inks in printed electronics, such as light-emitting diodes (LEDs)4, circuits5, flexible displays6, and radio frequency identification (RFID) tags7.…”
mentioning
confidence: 99%
“…One type is a suspension or dispersion of fine copper particles or nanoparticles1415161718192021. The other type is the copper-based metal-organic decomposition (MOD) ink, which is composed of a copper salt, amine/amino hydroxyl ligands and other organic components22425262728. Copper-based MOD ink, which has merits such as simplicity and scalability, has been studied for achieving high electrical conductivity at a low sintering temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation